Evaluation of poultry manure rates on growth and yield attributes of Kapok seedlings in Southeastern Nigeria - Praise-Gloria, Kalu Chidimma; Chiamaka, Chizaram-Ndubuaku; Kolawole, Olajide; Paul, Baiyeri Kayode (International Journal of Sustainable Agricultural Research, 2026)
A pot experiment examined the effect of poultry manure rates on Kapok seedlings’ growth by evaluating above- and below-ground biomass production at the Teaching and Research Farms of the Department of Crop Science, University of Nigeria, Nsukka. The experiment was laid out in a completely randomized design (CRD) with five replications. Poultry manure (PM) was applied at five treatment rates (0, 10, 20, 30, and 40 t ha-1) to Kapok seedlings, and parameters for growth and yield were measured at different time periods. Data collected were subjected to statistical analysis of variance (ANOVA). Results indicate that seedlings treated with 40 t ha-1 of PM showed consistent growth in plant height. Poultry manure rates had a significant effect (p < 0.05) on stem girth across the months, except at 2 MAT, with the application of 40 t ha-1 of PM consistently leading to greater stem girth measurements. A significant influence (p < 0.05) of PM rates was detected on the dry weight of shoot and whole seedling biomass, and the application of 40 t ha-1 of PM recorded higher yield values compared to other treatments. The application of poultry manure at 40 t ha-1 consequently favored increases in above- and below-ground biomass accumulation of Kapok seedlings, indicating its potential for organic production of Kapok seedlings.